Local economic development and poverty alleviation in rural areas of South Africa : a case of Makhuduthamaga Local Municipality, Limpopo Province - Mamogobo, Lenda Nthuteng (My University, 2021)
Local Economic Development (LED) has been practised in different countries to deal with poverty and unemployment at the local level. The success that the LED brought upon towards addressing these economic problems, led to the South African government to also undertake the LED initiatives to address poverty and unemployment that exist at the municipal level. Therefore, municipalities which are strategically closest to communities are responsible for poverty alleviation and employment creation in their local areas. The study sought to investigate the effectiveness of LED on poverty alleviation in rural areas of South Africa. The research objectives were as follows: to explore the concept of Local Economic Development, determine the types of poverty alleviation models and to assess the effectiveness of Local Economic Development to alleviate poverty in rural areas of South Africa. The study applied a semi-structured questionnaire and further considered literature review to achieve the research objectives focusing on Makhuduthamaga Local Municipality. A simple random sampling method was employed to select appropriately 100 participants in the study. Statistical Package for Social Sciences (SPSS) was used to process data, whilst, the content analysis method was also used for descriptive statistics. The study discovered that lack of resources including staff, skills and budget affect the undertakings of the LED activities in the communities negatively. Moreover, it was revealed that there is a need for community participation particularly towards successful implementation of the LED.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2021
Keywords: Local Economic Development.; Poverty alleviation.; Unemployment; Poverty -- South Africa; Economic Development -- South Africa; Unemployment -- South Africa